Max-dmin and P-OSM Precoders Performance for Robust and High Data Rate MIMO Transmissions in Underground Tunnels - Madi, G.; Nsiala Nzeza, C.; Vrigneau, B.; Cocheril, Y.; Berbineau, M.; Vauzelle, R. (2011 IEEE Vehicular Technology Conference (VTC Fall), 2011)
Multiple-input, Multiple-output (MIMO) techniques have proven their potentiality for transmissions in the public transport domain even in specific propagation context such as tunnels. When perfect channel state information (CSI) is available at the transmitter, performance improvement is allowed through a precoding operation. However, the performances of a such closed-loop MIMO system depend on the spatial correlation of the channel and the available CSI. In this paper, we considered three cases: an uncorrelated MIMO Rayleigh channel and two correlated channels in tunnel (medium and high correlation). The channel matrices are obtained by computing individual complex impulse responses using ray-tracing simulations with realistic geometric configurations of antennas in a one-way tunnel. The channel is then modelized thanks to the well-known Kronecker model. Therefore, we compared two recent precoders (max-dmin and P-OSM) based on the minimal Euclidean distance criterion. We demonstrated the full diversity of P-OSM and simulated the BER.